Analisis Pengalaman Pengguna Permainan Multiplayer Online Battle Arena (Moba) Dengan Menggunakan Game Experience Questionnaire (GEQ) Pada Game Dota 2 - Rachmad Soleh; Retno Indah Rokhmawati; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Multiplayer online battle arena (MOBA) is a genre of strategy video game, each player controls one "hero" on one team. MOBA provides a strong competitive atmosphere thereby providing a different experience to each of its users. DotA 2 is one of the most famous MOBA games. The user experience is very important for the success of a game. Playtesting method used to analyze the user experience of DotA 2 by using Game Experience Questionnaire (GEQ) as instrument to 25 respondents who have never played the game. The result of GEQ Core Module shows competance and negative effect significantly lower than median which proves that new users have no good ability and not feel the negative effects while playing DotA 2. In the GEQ Social Presence Module shows the highest average score obtained negative feelings that proves new users felt strongly negative feelings when playing with other players. While in the GEQ Post Game Module showed new users felt positive experience and not felt the negative experience, they felt tired and found it a bit hard to return to the real world after playing DotA 2.